Determining patterns of vascular function and structure in wild-type transthyretin cardiac amyloidosis. A comparative study. (15th September 2022) - Stamatelopoulos, Kimon; Delialis, Dimitrios; Georgiopoulos, Georgios; Tselegkidi, Maria-Irini; Theodorakakou, Foteini; Dialoupi, Ioanna; Bambatsias, Dimitrios; Petropoulos, Ioannis; Vergaro, Giuseppe; Ikonomidis, Ignatios; Tzortzis, Stavros; Briasoulis, Alexandros; et al.
Abstract: Background: The impact of wild-type transthyretin-related cardiac amyloidosis (ATTRwt) on functional and structural peripheral vascular measures is unknown. In the present study, we explored patterns of vascular dysfunction in patients with ATTRwt in comparison to diseases with similar cardiac phenotype. Methods: Treatment-naïve patients with ATTRwt (n = 32) were compared to: 1. Age-and sex-matched reference population without amyloidosis (n = 32), 2. Age-and sex-matched patients with systemic AL amyloidosis (n = 32), and 3. patients with cardiac AL amyloidosis (AL-HF, n = 23) or elderly patients with heart failure with preserved ejection fraction (HFpEF) (n = 16). All subjects underwent peripheral vascular assessment using carotid artery ultrasonography, brachial artery flow-mediated dilation (FMD), measurement of arterial stiffness and aortic hemodynamics including heart rate-adjusted time of return of reflected waves (Tr/HR). Results: After adjustment for traditional cardiovascular risk factors and coronary artery disease (core model), peripheral and aortic blood pressures (BP) were lower in patients with ATTRwt (p < 0.05) whereas other vascular markers were preserved compared to the reference non-amyloidosis group. ATTRwt was independently associated with lower BP and longer Tr/HR compared to AL. Compared to AL-HF, FMD was lower in ATTRwt (p = 0.033). ATTRwt patients had lower BP and higher Tr/HR than HFpEF (p < 0.05). By ROC analysis, Tr/HR discriminated ATTRwt vs. AL-HF (sensitivity 93%, specificity 75%) and HFpEF (sensitivity 100%, specificity 94%) and lower FMD increased the likelihood for ATTRwt at low Tr/HR values. Conclusion: ATTRwt patients present a distinct peripheral vascular fingerprint which is different from AL-HF or HFpEF, consisting of lower peripheral and aortic BP, prolonged Tr/HR and FMD at reference-population range. Highlights: ATTRwt is not associated with accelerated vascular aging or subclinical atherosclerosis ATTRwt patients present a preserved peripheral vascular fingerprint in comparison to HFpEF and cardiac AL ATTRwt vascular fingerprint consists of lower blood pressure and preserved arterial wave reflections and FMD Arterial wave reflections and FMD discriminate ATTRwt from cardiac AL and HFpEF beyond established cardiac biomarkers